A voice based text mail system for visually impaired - Mary Belinda M.J, Carmel; N, Rupavathy; N.R, Mahalakshmi (International Journal of Engineering and Technology, 2018)
To develop a voice primarily based email system that will facilitate visually impaired individuals to access email in a problem free    manner. Together with providing usage of mail services simply and with efficiency, the system also will cut back the psychological         feature work that must be unremarkably taken by the visually impaired to recollect and sort characters using the normal Braille          keyboards, which are accessible to them. The graphical user interface of this method has been evaluated against the interface of the traditionally accessible mail system. Not only for visually impaired, but also for  people who are illiterate might have the benefit of this technique. The foremost crucial facet which will be thought of developing this technique is that the users of this technique does not have any basic information regarding the keyboard shortcuts used or wherever the keys are used for. All functions to be  utilized in this technique are supposed to be easy mouse click operations creating the system very user friendly. This application                       proposes an android application, designed specifically for visually impaired individuals. This application provides a voice primarily based mailing service which provides them to browse and send mail on their own, without any guidance. The users ought to use certain keywords which can perform certain actions for e.g. Read, Send, Compose Mail, Address Book etc. This EMAIL         system is utilized by a visually handicapped person to access mails easily and with efficiency. Therefore reliance of visually impaired on others for his or her own activities associated with mail are often reduced.